PENERAPAN WEB SERVICE UNTUK SISTEM MANAJEMEN PERPUSTAKAAN PADA PERPUSTAKAAN DAERAH KABUPATEN KUDUS DENGAN METODE RESTFUL - Rizq Alwan Fauzan; Mukhamad Nurkamid; Rizkysari Meimaharani (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2023)
A web service or also known as a web Application Programming Interface (API) is a service that opens two or more independent systems that can communicate with each other, a Web service is created so that the library management system in the archives and library services of Kudus Regency can interact with other systems even though there are differences in the format, operating system, and programming language used between the client and server. The waterfall method is the method used by researchers in developing this system. This method is carried out with a systematic approach, the stages in this method are system requirements analysis, system design, program code generation, testing, and maintenance. Thus, this system is expected to be able to become an intermediary in exchanging data between one system and another, so that it can provide convenience for system managers to connect new systems with existing systems in the archives and library services of Kudus Regency without changing the existing system. been up and running before.